Topological boundaries of covariant representations - Amini, Massoud; Zavar, Sajad (MATHEMATICA SCANDINAVICA, 2023)
We associate a boundary B_π ,u to each covariant representation (π ,u,H) of a C^*-dynamical system (G,A,α ) and study the action of G on B_π ,u and its amenability properties. We relate rigidity properties of traces on the associated crossed product C^*-algebra to faithfulness of the action of the group on this boundary.